Estructuración del sistema de aseguramiento de la calidad total para la empresa Codepret S.A. ubicada en el norte de la ciudad de Quito, dedicada a la comercialización de recargas físicas y electrónicas de todas las operadoras. - Medrano Suárez, Verónica Elizabeth (2013)
This structuring of the quality system is based on international standards ISO 9001 aimed at ensuring the quality of service provided Codepret was generated documents comprising the same, such as the Quality Manual, Manual Process and the different stages forward for the implementation and development of the system.